Applied aspects of systems structural-topological characteristics calculation - SichkoТ. V.; Smoktii, K. V.; TkachukА. О. (Systems and Technologies, 2019)
Often happens that for the analysis of the system structural properties on a graphmetric characteristics are inconsequential, at the same such topological nature parametersas connectivity, compactness and continuity are valuable. The-se characteristics allow optimizing structural links between elements of any sys-tem according to different criteria using structural-topological analysis of sys-tems, which play important role for social and economic development of any country. In this paper we analyzed the existing applications for graph processing and took into account purchasing costs (that can be licensed use) and concluded that it isadvisable to develop a web application that would be an open source code (free to use) and to perform the calculation of the basic characteristics for the structural analysis of the systems that are described by the graph model, for instance: connectivity, continuity, redundancy, compactness, hierarchy, diameter, uneven distribution of bonds. Applied aspects of the calculation of systems structural-topological charac-teristics are considered and an approach as for the automation of systems struc-tural-topological characteristics calculations is developed. This approach allows to synthesize the corresponding web application with its publication in the Inter-net for further use for the decision-making process concerning the optimization of the structural relations of the investigated system. Single-page format was chosen as one of the most widespread and most convenient to use for the web-application. A single-page application is a web ap-plication that uses a single HTML document as a shell for all web pages and or-ganizes user interaction through HTML, CSS, and JavaScript files that are dy-namically loaded. Developed application is connected to the version control sys-tem Git, downloaded to Git Hub and connected to Git Hub Pages. As an example, the organizational structure of the game developing company is considered and needed calculations of the system characteristics are done. The conclusions from this research and the prospects for further improvement of the developed one-page application are presented.